The Comparison of Learning Achievement, Retention, and Emotional Quotient of Kings Speech of Prathom Suksa 6 Students between the Role Play and BBL - ฉิมรักษ์, รังสิมันตุ์ (RMUTI Journal Humanities and Social Sciences, 2015)
The purposes of the study were to 1) Determine the efficiency of the lesson Plan, the terms of reverence Grade 6 has been organized a role play and BBL as effective as the standard 80/80 2) Find the value effectiveness index of lesson plans about the reverence Grade 6 has been a role-play activities and BBL 3) Compare achievement Durability and emotional intelligence grade 6 student to learn about the secrets with a role-play event with BBL samples used in the research, Prathomsuksa 6 of 40 students from the school’s Ram 2, which is purposive sampling. Instruments used in the study are three types of plan learning activities and the role and activities within learning BBL model 9 percent plan to test achievement types optional 4 options 40 items which. The difficulty ranging from 0.62 to 0.75, the discrimination ranging from 0.26 to 0.49 and the confidence interval, 0.92 reliability. A five - rating scale and 30 items emotional quotient test with discriminating power between 0.20 to 0.75 and 0.74 reliability statistics used in data analysis were percentage, mean, standard deviation. And hypothesis testing using t-test (Independent Samples). The results were as follows 1. Efficiency of learning activities, role play, with the reverence of a student’s Grade 6 performance was 85.75/84.62 and 83.54/80.37. 2. The index of the effectiveness of the learning activities and role-play with the royal word of the students grade 6 the effectiveness index of 0.7713 and 0.6616, indicating that students are progressing in learning more equal 77.13 and 66.16 percent. 3. Pupils who have been learning activities and role-play with the achievement of durable and emotional intelligence was higher than the group that was organized learning BBL significant statistical at level 0.01.